2007
DOI: 10.1093/humupd/dmm008
|View full text |Cite
|
Sign up to set email alerts
|

Among patients treated with FSH and GnRH analogues for in vitro fertilization, is the addition of recombinant LH associated with the probability of live birth? A systematic review and meta-analysis

Abstract: The aim of this systematic review and meta-analysis was to assess whether the addition of recombinant luteinizing hormone (LH) increases live birth rate, among patients treated with follicle stimulating hormone (FSH) and gonadotrophin-releasing hormone (GnRH) analogues for in vitro fertilization (IVF). Eligible studies were randomized controlled trials (RCTs) answering the research question that contained sufficient information to allow ascertainment of whether randomization was true and whether equality was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 21 publications
3
47
2
2
Order By: Relevance
“…A similar result was reported in a meta analysis on seven randomized clinical trials which rLH added to rFSH in GnRH agonist protocols [46]. Although all patients in this study were selected from a poor respond population, no cycle cancellation was noted in three groups during the treatment cycle.…”
Section: Variablesupporting
confidence: 85%
“…A similar result was reported in a meta analysis on seven randomized clinical trials which rLH added to rFSH in GnRH agonist protocols [46]. Although all patients in this study were selected from a poor respond population, no cycle cancellation was noted in three groups during the treatment cycle.…”
Section: Variablesupporting
confidence: 85%
“…A previous meta-analysis of randomised controlled trials showed that pregnancy and live birth rates were not different between cycles using rLH supplementation versus rFSH alone [11]. However, it was cautioned in this review that the sample size available through the 7 RCTs was not adequate to determine clinical significance.…”
Section: Discussionmentioning
confidence: 87%
“…Prior meta-analyses have not suggested any improvement in pregnancy outcomes with LH supplementation [11,16]. However, a recent study of normogonadotrophic women showed an increase in the number of oocytes collected, number of oocytes in metaphase II, fertilization rate, implantation rate and live birth rate in those that had LH supplementation [9].…”
Section: Introductionmentioning
confidence: 98%
“…It was suggested that the exogenous addition of LH may be of benefit in this subgroup of women in order to improve IVF outcomes [10]. The use of LH for IVF stimulation is a debated issue in the literature and it has not been shown a [19,20]. Moreover, the role of the supplementation of LH in the women with high basal FSH/LH ratio and lower LH concentration has not been investigated.…”
Section: Discussionmentioning
confidence: 99%